Investigation of the Effect Of 5lp Liners on Seed Lintering Process and Product Quality in A 30-Saw Stand View with Existing and Improved Blade Mixers - Nomanov Mirjalal Abdumalikovich (Scientific Trends, 2024)
Comparison-experimental work was carried out in laboratory conditions on the 5LP linter with an improved mixer 30 saw, with selected blades bent 60 degrees towards the rotation of the seed roller with the existing mixer 30 saw linter. In the comparison work, it was studied that the productivity of the linters, the quality of the produced seed and fluff in the proposed mixer linter, when the distance between the saw cylinder and the mixer blades is changed by 9-12 mm, is higher than that of the 30-saw linter with the existing mixer. Especially, during the period of comparison-experimental work, when the distance of the improved blade mixer with a saw cylinder is changed by 9-10 mm, the hairiness level of the seed produced from the linter of Namangan-77 selection grade I technical seed in the 5LP linter is on average 6.78% to 7.0%. UzDst 596:2016 showed that it fulfilled the requirements of the state standard. The quality of seed produced improved from 0.33 (abs)% to 0.17 (abs)%, and the quality of lint improved from 0.54 (abs)% to 0.8 (abs)% compared to the quality of seed produced from the existing mixer linter. In this case, the linter's seed productivity was 28 kg/h and 10 kg/h higher than the existing mixer linter's seed productivity. The staple length of the produced fluff was 6/7 mm, it was one class higher than the improved quality and according to the state standard UzDst 645:2016, it corresponded to the class I grade B type "Middle". The results of the comparison-experimental work conducted on the 5LP linter with 30 blades showed that the efficiency of the linter with improved mixing blades is higher than the efficiency of the linter with the existing design mixer. In the proposed mixing linter, the distance between the saw teeth in the saw cylinder with the improved blades in the mixer is 9 mm and 10 mm. it was recommended to take 12 mm when lintering seeds .
Keywords: Linter, mixer, parrrack, saw cylinder, saw, seed, lint, performance, hairiness, damage, dirt, quality.